Enterprise Architecture on Moral-based School Education Information Systems - Sopian, Adi; Karlina, Haura; Saefurridjal, Achmad; Fatkhullah, Faiz Karim (Politeknik Ganesha Medan, 2023)
Indonesia has a diversity of cultures, hospitality, and people who have good ethics. Moral problems often occur and are commonplace, such as corruption, collusion, nepotism, promiscuity and drug abuse, sexual harassment, theft, and murder. The Indonesian nation experienced moral degradation. Moral education refers to the concept of Moral Behavior. Ethical behavior is grouped into three parts: Moral Attitudes, Moral Feelings, and Moral Thoughts. Moral education is very dependent on how to educate parents, association, and the community environment. Moral issues are not enough just to do an analysis of moral education, such as the perspective of religion, philosophy, psychology, and sociology. But also provide solutions so that moral improvement can occur. One of the solutions for improving morale is, of course, by providing education for moral improvement, such as establishing a school with the aim of improving morale. This is what drives the establishment of schools based on moral education, which use the perspectives of religion, philosophy, psychology and sociology. One of the proposals is moral-based education with the help of information technology. Information technology is capable of performing tasks such as controlling the behavior of students, teachers, and being able to control content that is not in line with the educational curriculum. The results of monitoring students can be reported online at any time. This research aims to provide moral improvement solutions by establishing a moral-based school, with the help of Enterprise Architecture as a Framework. This Enterprise Architecture output is an Information Technology Blueprint for system development in schools. The approach used is the Framework from The Open Group Architecture Framework.